Book Reviews - Rosenblatt, Arnold; Davis, Bret (Columbia Journal of Environmental Law, 2020)
NUCLEAR NONPROLIFERATION: THE SPENT FUEL PROBLEM. Edited by Frederick C. Williams and David A. Deese. New York: Pergamon Press. 1979. Pp. xi, 221. $30.00. WILDERNESS ECONOMICS AND POLICY. By Lloyd C. Irland. Lexington, Mass.: D.C. Heath & Co. 1979. Pp. xviii, 225. $18.95.